2019
DOI: 10.1038/s42005-019-0200-2
|View full text |Cite
|
Sign up to set email alerts
|

Observation of spin–orbit coupling induced Weyl points in a two-electron double quantum dot

Abstract: Recent years have brought an explosion of activities in the research of topological aspects of condensed-matter systems. Topologically nontrivial phases of matter are typically accompanied by protected surface states or exotic degenerate excitations such as Majorana end states 1,2 or Haldane's localized spinons. 3,4 Topologically protected degeneracies can, however, also appear in the bulk. An intriguing example is provided by Weyl semimetals, where topologically protected electronic band degeneracies and exot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 39 publications
4
39
0
Order By: Relevance
“…Since interaction with the tip creates excess carriers in an extremely localized region due to the small tip radius (~20 nm), exciton density in the region is dramatically higher as opposed to far-field excitation at same total power, hence the formation of stable biexcitons at room temperature. The stable biexciton formation in our case is supported by the prior report about resonant excitation of CsPbBr 3 perovskite nanoplate inside the Ag nanowire-Ag film plasmonic nanogaps 53 , which reported that the necessary exciton occupancy for excitation was significantly reduced by~10 6 times from the plasmonic gap. We rule out the possibility of detrimental influence of the Purcell effect on MoSe 2 since plasmonic resonators are well known for large and reproducible enhancement of spontaneous emission 52,[54][55][56] .…”
Section: Correlation Of Nanoscale Features Using Tip-enhanced Photolusupporting
confidence: 87%
“…Since interaction with the tip creates excess carriers in an extremely localized region due to the small tip radius (~20 nm), exciton density in the region is dramatically higher as opposed to far-field excitation at same total power, hence the formation of stable biexcitons at room temperature. The stable biexciton formation in our case is supported by the prior report about resonant excitation of CsPbBr 3 perovskite nanoplate inside the Ag nanowire-Ag film plasmonic nanogaps 53 , which reported that the necessary exciton occupancy for excitation was significantly reduced by~10 6 times from the plasmonic gap. We rule out the possibility of detrimental influence of the Purcell effect on MoSe 2 since plasmonic resonators are well known for large and reproducible enhancement of spontaneous emission 52,[54][55][56] .…”
Section: Correlation Of Nanoscale Features Using Tip-enhanced Photolusupporting
confidence: 87%
“…6(d,e) reflects unique local fingerprints and colossal magnitude of the orbital magnetization m z (k) in momentum space which correlate with the emergence of we anticipate that these coupling phenomena can play a key role even in finite systems such as quantum dots (see, for example, Ref. 64). Analogously, we envisage that complementing the topological classification of matter by magnetic information rooting in the electronic degrees of freedom will be valuable for other research fields as well, e.g., for topological magnon semimetals 65,66 .…”
Section: Resultsmentioning
confidence: 93%
“…In Refs. [81,82], the authors find that topologically protected magnetic degeneracy points (referred to as magnetic Weyl points) can appear in DQDs for arbitrary SOI; i.e., for certain orientations of the magnetic field ±B W , the singlet |S and the lower triplet state |T − become degenerate: the levels cross as function of magnetic field and are protected from hybridization. In the DQD system considered here, the decoupling of the T ± states from the ST 0 states also leads to magnetic degeneracy points at fine-tuned magnetic fields.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, many of the recent experimental setups seem to be invariant under reflection with respect to a certain plane, e.g., the plane being perpendicular to the plunger gates in Refs. [40,81]. Since the orientation of the magnetic field is usually tunable via a two-or threedimensional vector magnet, the study of anisotropic effects is well within the reach of state-of-the-art experiments.…”
Section: Discussionmentioning
confidence: 99%